2019
DOI: 10.1055/a-0958-9548
|View full text |Cite
|
Sign up to set email alerts
|

MRI Brain Changes After Marathon Running: Results of the Berlin Beat of Running Study

Abstract: Several studies report neurological complications such as brain injury induced by ischemia or edema following exhaustive endurance sport. We aimed to detect the frequency of acute brain lesions after a marathon race. In the prospective observational Berlin Beat of Running study, 110 experienced endurance athletes underwent 3-Tesla brain MRI exams 2–3 days prior and within 2 days after a marathon run. MRI results were compared to an age- and sex-matched control group of 68 non-athletes, including the “Age-Relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…Subtle reversible volume decreases in global gray matter, but not in white matter, in ultramarathon multistage runners have been reported earlier with no other signs of brain changes and damage, as determined by MRI and evaluations for neurological complications. [20][21][22][23] This reduction and subsequent recovery were paralleled by a similar loss in body weight and was gained following a period of rest. 21 Interestingly, EEG activity increases bilaterally in all brain lobes during graded exercise, correlates with its intensity, and returns to resting levels quickly after cessation of exercise.…”
Section: Discussionmentioning
confidence: 90%
“…Subtle reversible volume decreases in global gray matter, but not in white matter, in ultramarathon multistage runners have been reported earlier with no other signs of brain changes and damage, as determined by MRI and evaluations for neurological complications. [20][21][22][23] This reduction and subsequent recovery were paralleled by a similar loss in body weight and was gained following a period of rest. 21 Interestingly, EEG activity increases bilaterally in all brain lobes during graded exercise, correlates with its intensity, and returns to resting levels quickly after cessation of exercise.…”
Section: Discussionmentioning
confidence: 90%
“…Möhlenkamp et al 32 reported initial findings in 2008 and then 3 other studies later provided further analysis concerning the MRFs. 23,33,35 Similarly, Haeusler et al 19,20 later reported findings in 2 related papers that provided information in relation to the aims of the study and follow-up data. Finally, Schwartz et al 53 provided subsequent analysis in a related paper on the MRFs of marathon runners.…”
Section: Search and Study Selection Resultsmentioning
confidence: 99%
“…The assessment for MRFs varied across the 5 studies. 18,22,32,53,57 Most of the studies used a combination of the following: medical history 18,22,32,53,57 ; marathon race history 18,22,32,53,57 ; physical examination 18,22,32,53,57 ; blood analyses 18,22,32,53,57 ; sociodemographic history 18,19,20 ; Framingham risk score (FRS) 23,32,33,35 ; Rose angina questionnaire 23,32,33,35 ; nonvalidated questionnaires, 23,32,33,35 for example on lifestyle, 48,53 health, nutrition, exercise, and psychosocial and socioeconomic risk factors; interviews 23,32,33,35 ; Prospective Cardiovascular Münster (PROCAM) cardiovascular study CV risk score 57 ; BORG rating of perceived exertion scale 22 ; and an exercise treadmill stress test (GXT). 22 It was difficult to compare these data as not all studies followed specific criteria that can be noted in their measurement of BP and recall data, which could influence bias.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A possible confounding effect on assimilating MWF to myelin content is brain edema, which may occur in strenuous exercise like high mountain ultramarathons but has not been observed in 42.195 m marathons ( 54, 55 ). Moreover, edema/inflammation during new lesion formation in multiple sclerosis has a minor impact, if any, on MWF ( 56 ).…”
Section: Supplementary Materialsmentioning
confidence: 99%